State Variation in Certifying Manner of Death and Drugs Involved in Drug Intoxication Deaths. Issue 2 (June 2013) - Warner, Margaret; Paulozzi, Leonard J.; Nolte, Kurt B.; Davis, Gregory G.; Nelson, Lewis S.
National statistics on drug intoxication deaths are based solely on data derived from death certificates. This study examines the variation in the manner of death classification by state, and the specificity of drugs involved in drug intoxication deaths by state and by type of death investigation system. The National Vital Statistics System Multiple Cause of Death mortality files (2008–2010) were analyzed. Drug intoxication deaths were those with ICD-10 Underlying Cause of Death of X40-X44 (unintentional), X60-X64 (suicide), X85 (homicide), or Y10-Y14 (undetermined intent). Among drug intoxication deaths, deaths involving non-specified drug(s) were those with Multiple Cause of Death (MCOD) of T50.9, and no MCOD in the range T36-T50.8. State death investigation systems were categorized as follows: centralized state medical examiner offices, county/district medical examiners, hybrid, and decentralized county coroners. In 2008–2010, there was an average of over 37, 250 drug intoxication deaths per year in the U.S. The manner was undetermined for 8% for the U.S., ranging from 1% to 85% among the states. During 2008–2010, 75% of the drug intoxication deaths had at least one specific drug reported on the death certificate. States with centralized state medical examiner systems had a higher percent (92%) of drugs specified than did those with other systems. Across the U.S., there is variation in the percent of drug intoxication deaths classified as having undetermined manner of death and with specific drugs identified on death certificates. This variation has significant implications for public health surveillance and for prevention efforts.